Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1158/0008-5472.can-06-3212
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chemical Enhancers of Heat Shock Increase Thermal Radiosensitization through a Mitotic Catastrophe Pathway

Abstract: Radiation therapy combined with adjuvant hyperthermia has the potential to provide outstanding local-regional control for refractory disease. However, achieving therapeutic thermal dose can be problematic. In the current investigation, we used a chemistry-driven approach with the goal of designing and synthesizing novel small molecules that could function as thermal radiosensitizers..2]octan-3-ol was identified as a compound that could lower the threshold for Hsf1 activation and thermal sensitivity. Enhanced t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…In a recent report, we have shown that a novel heat enhancer reduces the threshold for both heat radiosensitization and the heatinduced delay in 53BP1 complex formation (48). Thus, rapid assays using the heat-induced delay of 53BP1 complex formation as a readout could be used to screen for heat enhancers and heat mimics.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, we have shown that a novel heat enhancer reduces the threshold for both heat radiosensitization and the heatinduced delay in 53BP1 complex formation (48). Thus, rapid assays using the heat-induced delay of 53BP1 complex formation as a readout could be used to screen for heat enhancers and heat mimics.…”
Section: Discussionmentioning
confidence: 99%
“…17,18), histone acetyltransferase depleting agents (19), and microtubule disruption agents (20). So, targeting cancer cells to undergo mitotic catastrophe is also considered to be a new efficacy strategy to overcome the drug or radiation resistances in cancer therapy (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…α-tubulin expression was analyzed in all the experiments as internal control. radiosensitization, 25,26) and inhibitors of matrix metalloproteinase 3 (MMP-3) enhanced heat shock-induced cell death in HeLa cells. 27) In contrast to these compounds, 5-ALA is a natural amino acid with no toxic side effects on normal cells.…”
Section: Discussionmentioning
confidence: 99%